Notes sur la Vie de S. Samuel de Kalamon. Versions arabe et éthiopienne - Deux citations de la "prière de la fraction" - Zanetti, Ugo (Analecta Bollandiana, 1997)
St Samuel of Kalamon was an Egyptian monk who died 695 A.D. His Life (attested to in Coptic, Arabic, and Ethiopian) contains, inter alia, an allusion to one of the "prayers of the Fraction" that the Coptic Church uses today during Lent. This, and other liturgical and philological observations, enables us to sketch out the relationship among the various recensions.